A REVIEW ON FEMALE EXECUTIVE COMPENSATION GAP - Yingkun Lyu; Dr Irfah Najihah Binti Basir Malan (International Journal of Accounting, Finance and Business, 2022)
With the development of economy, women can be considered as an important partof labor force. However, gender difference has long been an important issue in workplace paygap, how to gradually solve the gender pay inequity problem is a worldwide difficult problem,it is also one of the indicators to measure the economic development of a country or a region.When the perspective is focused on the gender difference in executive compensation, the genderpay gap still exists, however, research attention on this issue is not enough, so it is become aproblem worth thinking about. Therefore, this paper focused on executive gender pay gap, thereasons are analyzed based on the current situation of gender differences in executive pay, andthen several suggestions are highlighted to overcome these problems.